The last time she saw him ebook A novel. - White, Kate (2024)
Picked as one of "This Week's Hottest Reads" by Katie Couric Media A woman is left reeling when her former fiancé appears to take his own life, and she becomes desperate to prove it was actually murder—in the latest psychological thriller from New York Times bestselling author Kate White As Kiki Reed heads out to a party at a friend's house in the Connecticut countryside, she's more than a little nervous. Her ex-fiancé Jamie, a great guy who just wasn't "the one," will be attending, and she hasn't seen him since she broke his heart a few months earlier. But when they come face to face, their exchange is brief and pleasant, which is a huge relief. Then, as the party is winding down, a noise pierces the night. The last few guests run outside to find Jamie inside his car, dead from a gunshot wound. Shocked and grieving, Kiki learns that the police believe Jamie took his own life, but she knows he was moving on from the breakup and just doesn't believe it. Determined to find the truth, she searches for any evidence that will get the police to take her seriously. But as she peels away the layers, she uncovers something far more sinister than she'd imagined—and it may be her life on the line next. . .